A reexamination of spreading of position-effect variegation in the white-roughest region of Drosophila melanogaster. - Talbert, P.B.; Henikoff, S. (Genetics, 2000)
In Drosophila, heterochromatin causes mosaic silencing of euchromatic genes brought next to it by chromosomal rearrangements. Silencing has been observed to "spread": genes closer to the heterochromatic rearrangement breakpoint are silenced more frequently than genes farther away. We have examined silencing of the white and roughest genes in the variegating rearrangements In(1)w(m4), In(1)w(mMc), and In(1)w(m51b). Eleven stocks bearing these chromosomes differ widely in the strength of silencing of white and roughest. Stock-specific differences in the relative frequencies of inactivation of white and roughest were found that map to the white-roughest region or the adjacent heterochromatin. Most stock-specific differences did not correlate with gross differences in the heterochromatic content of the rearranged chromosomes; however, two stocks, In(1)w(m51b) and In(1)w(mMc), were found to have anomalous additional heterochromatin that may act in trans to suppress variegating alleles. In comparing different stocks, the frequency of silencing of the roughest gene, which is more distant from heterochromatin, does not correlate with the frequency of silencing of the more proximal white gene on the same chromosome, in contradiction to the expectation of models of continuous linear propagation of silencing. We frequently observed rough eye tissue that is pigmented, as though an active white gene is skipped.